Avaliação clínica de um gel de nitrato de potássio e flúor na diminuição da sensibilidade no clareamento caseiro - Kose Junior, Carlos (2010)
The aim of this double-blind randomized clinical study was to evaluate whether the use of a desensitizing agent (5% potassium nitrate and 2% sodium fluoride [Desensibilize KF 2%, FGM]) before at-home bleaching would prevention/decrease tooth sensitivity when compared to a placebo. Sixty caries-free patients, over 18 years were divided into desensitizer and placebo groups. Before at-home bleaching with 16% carbamide peroxide gel (Whiteness Standard, FGM) under night, a placebo or desensitizer gel was applied in the tray and using by patients for 10 min. The same bleaching protocol was repeated for 4 weeks for both groups. The patients recorded their perception of tooth sensitivity on a 0-4 scale. For color changes at each two-week recall for both groups was evaluated for a repeated measures two-way ANOVA and Tukey´s test (α=0.05). The percentage of patients with tooth sensitivity were analyzed using the Fisher's exact test. The different levels of sensitivity were analyzed using the Fisher's exact test or Chi-square test, and the intensity of sensitivity were analyzed using the Student's t-test (α=0.05). The use of desensitizing gel did not affect the bleaching efficacy of the carbamide peroxide agent (p>0.05). The tooth sensitivity frequency was similar for both groups (66,6% for placebo and 63,3% for desensitizer group; p=0.93). The number of days without sensitivity was more frequency in the desensitizer group, despite no significant difference was found (p>0.05). However, the intensity of sensitivity was higher for the placebo (1.51 ± 0.51) compared to the desensitizer group (1.16 ± 0.52) (p=0.009). The use of the desensitizing gel based on 5% nitrate potassium and 2% sodium fluoride before the at-home bleaching regimen with 16% carbamide peroxide does not affect the bleaching efficacy and reduce the tooth sensitivity intensity.